2015
DOI: 10.1890/es14-00176.1
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment, abundance, and predation on the blue mussel (Mytilus edulis) on northeastern estuarine rocky shores

Abstract: Abstract. We report on patterns of abundance, recruitment, and predation on the blue mussel (Mytilus edulis) in three human-dominated estuaries in the northeastern United States. Through replicate field experiments and observational studies at multiple sites nested within each of the three estuaries, we investigated the relative influences of local and regional scale variation in select bottom-up and top-down factors on blue mussel populations on wave-protected rocky shores. The most striking result was the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
(84 reference statements)
0
7
0
2
Order By: Relevance
“…These K-S interactions between green crabs and dogwhelks feeding on the same blue mussel prey represented a component of the IGP, TMII/BMII, and trophic interactions in this system, with probable impacts on mussel survival and population growth, and subsequently on mussel bed ecosystem dynamics , Cockrell et al 2015, Trussell et al 2017, and yet they had not been reported previously. However, this tritrophic system is by no means unique, as many bivalves throughout the world are consumed by both shell-drilling gastropods and crabs (Carriker & Williams 1978, Kowalewski 2002, Ishida 2004, Klompmaker et al 2019.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…These K-S interactions between green crabs and dogwhelks feeding on the same blue mussel prey represented a component of the IGP, TMII/BMII, and trophic interactions in this system, with probable impacts on mussel survival and population growth, and subsequently on mussel bed ecosystem dynamics , Cockrell et al 2015, Trussell et al 2017, and yet they had not been reported previously. However, this tritrophic system is by no means unique, as many bivalves throughout the world are consumed by both shell-drilling gastropods and crabs (Carriker & Williams 1978, Kowalewski 2002, Ishida 2004, Klompmaker et al 2019.…”
Section: Introductionmentioning
confidence: 58%
“…Bivalve molluscs (clams, cockles, mussels, oysters, scallops, etc.) are filter-feeding organisms that form the bases of many aquatic food webs in both marine and freshwater environments (Seed 1976, Cockrell et al 2015. Bivalves are important food sources for a wide variety of secondary and higher-level consumers, including decapod crustaceans, gastropod molluscs, polychaete worms, fishes, birds, humans, and many others (Seed 1976, Hamilton 2000, Morissette & Himmelman 2000, Trussell et al 2017, and also play roles in controlling habitat structure (Enderlein & Wahl 2004) and community diversity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluctuations in the abundance of sessile bivalve populations, including those of dreissenids, have been explained by invoking effects of internal and/or external drivers. The former involve primarily recruitment and mortality (e.g., Cockrell et al, 2015;Polsenaere et al, 2017) and intra-specific competition (e.g., Naddafi et al, 2010;D'Hont et al, 2018) as mechanisms of population regulation (Krebs, 1995). In the D. polymorpha population studied here, recruitment might have played a role, as the abundance peaks coincided with the appearance of new cohorts, visible as increased numbers of small (<8 mm) individuals in the population (Wawrzyniak-Wydrowska et al, in prep.).…”
Section: Discussion Dreissenid Abundance and Biomassmentioning
confidence: 89%
“…The distribution of mussels along the northeast coast of the United States in the intertidal is noteworthy for being associated with rocky shores or manmade structures(Cockrell, Bernhardt, & Leslie, 2015;Lauenstein et al, 1997), although they commonly occur in intertidal mats along the western European coast(Beukema & Cadée, 1996;Diederich, 2006). The abundance of cobbles and rocks at some survey sites suggests ideal substrate exists for mussels and sites yielding mussels or cobbles and rocks in abundance were often located in a similar depth range along a southeast trending line from the northwestern corner of the HMA south to the central region of the HMA (Figure7).…”
mentioning
confidence: 99%